La educación ambiental y su relación con los ejercicios prácticos para conservar la naturaleza en el proceso de enseñanza-aprendizaje en los niños y niñas del primer año de educación básica de las Escuelas Fiscales Mixtas Amelia Tobar y John F. Kennedy de la ciudad de Pasaje, período 2012-2013. - Gonzaga Barreto, Paola Rebeca (2014)
The development of this thesis entitled ENVIRONMENTAL EDUCATION AND ITS RELATIONSHIP WITH PRACTICAL EXERCISES FOR NATURE PRESERVE IN THE LEARNING PROCESS IN CHILDREN FIRST YEAR BASIC EDUCATION HIGH SCHOOL MIXED TAX AND JHON TOBAR AMELIA F. KENNEDY OF THE CITY OF PASSAGE, PERIOD 2012-2013,is a research diagnosis – purposeful aimed at determining the relationship between environmental education and practice exercises for the conservation of nature in children's First Year of Basic General Education, for what developed a methodological process based on inductive, deductive, descriptive, statistical methods and the hypothetical. Regarding the use of techniques, observation, interview, surveys and signing were used. The investigative process made it possible to reach the conclusion that the relationship between environmental education and practical exercises for the conservation of nature in the first year of basic General education, is of great importance to Good living, since it allows the child and girl from an early age have ecological conscience and with help to the conservation of nature and of life on planet Earth However the environmental education in the first year of basic General education in the selected schools, is characterized by being little active, since teachers have limited training, what causes children who during the classes are barely interested in preserving the environment, this is aggravated by the fact that the activities developed by the teacher in the process teaching-learning, they are not original or stimulating, majority are extracted from the text which consist of drawing Paint, cut, and paste.